2020
DOI: 10.1111/anu.13182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spirulina powder ( Spirulina platensis ) as a dietary additive on Oscar fish, Astronotus ocellatus : Assessing growth performance, body composition, digestive enzyme activity, immune‐biochemical parameters, blood indices and total pigmentation

Abstract: In this study, the effect of spirulina meal (Spirulina platensis) as a feed additive on growth and physiological response of Oscar fish,Astronotus ocellatus, was assessed using four diets including control without spirulina supplementation, 13.75 g/kg spirulina (SP1), 27.50 g/kg spirulina (SP2) and 55 g/kg spirulina (SP3). One hundred and twenty fish (10.41 ± 0.25 g) were disturbed to twelve aquariums and fed to apparent satiation three times a day for 8 weeks. The result showed that the SP3 treatment had stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…Recent studies demonstrated that long-term feeding with curcumin markedly enhanced the protein and ash contents of Nile tilapia muscles (Abd El-Hakim et al, 2020; Amer et al, 2022). Similar results were reported in Oscar sh, Astronotus ocellatus fed SP powder (Mohammadiazarm et al, 2021). Dietary SP increased the ash content of whole body and dorsal muscles along with signi cant decreased in lipid content in the juvenile gibel carp (Cao et al, 2018b).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Recent studies demonstrated that long-term feeding with curcumin markedly enhanced the protein and ash contents of Nile tilapia muscles (Abd El-Hakim et al, 2020; Amer et al, 2022). Similar results were reported in Oscar sh, Astronotus ocellatus fed SP powder (Mohammadiazarm et al, 2021). Dietary SP increased the ash content of whole body and dorsal muscles along with signi cant decreased in lipid content in the juvenile gibel carp (Cao et al, 2018b).…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, a signi cant increment in the lysozyme mRNA expression was observed in the Cu-NPs fed L. vannamei shrimp (Bhoopathy et al, 2021). A rmative effects of spirulina platensis on the inherent immunity of sh, including lysozyme activity were noticed earlier (Awad et al, 2022;Cao et al, 2018a;Mohammadiazarm et al, 2021). Our nding may be accompanied by the induction of the humoral immunity of Nile tilapia after Cu-NPs and SP administration as curcumin provokes cytokines production with activating of macrophages and neutrophils, which regulate the immunity response of sh (Jagetia and Aggarwal, 2007).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The past decades have seen an increase in the trade of ornamental sh, about US$44 million annually (FAO 2019). But, the crucial points for developments in the ornamental sh industry are the improvement of coloration, immunity system, and survival rate of sh (Mohammadiazarm et al 2021). Therefore, the commercial sh breeders try to use supplemental additives in formulated feeds for higher pro ts in ornamental sh trades.…”
Section: Introductionmentioning
confidence: 99%